Microarray Analysis of Gene Expression Profiles in Response to Treatment with Melatonin in Lipopolysaccharide Activated RAW 264.7 Cells - Ban, Ju Yeon (The Korean Physiological Society and The Korean Society of Pharmacology, 2011)
Melatonin, which is the main product of the pineal gland, has well documented antioxidant and immune-modulatory effects. Macrophages produce molecules that are known to play roles in inflammatory responses. We conducted microarray analysis to evaluate the global gene expression profiles in response to treatment with melatonin in lipopolysaccharide (LPS) activated RAW 264.7 macrophage cells. In addition, eight genes were subjected to real-time reverse transcription polymerase chain reaction (RT-PCR) to confirm the results of the microarray. The cells were treated with LPS or melatonin plus LPS for 24 hr. LPS induced the up-regulation of 1073 genes and the down-regulation of 1144 genes when compared to the control group. Melatonin pretreatment of LPS-stimulated RAW 264.7 cells resulted in the down regulation of 241 genes and up regulation of 164 genes. Interestingly, among genes related to macrophage-mediated immunity, LPS increased the expression of seven genes (Adora2b, Fcgr2b, Cish, Cxcl10, Clec4n, Il1a, and Il1b) and decreased the expression of one gene (Clec4a3). These changes in expression were attenuated by melatonin. Furthermore, the results of real-time PCR were similar to those of the microarray. Taken together, these results suggest that melatonin may have a suppressive effect on LPS-induced expression of genes involved in the regulation of immunity and defense in RAW 264.7 macrophage cells. Moreover, these results may explain beneficial effects of melatonin in the treatment of various inflammatory conditions.